VARIASI PEMEROLEHAN BAHASA PERTAMA PADA ANAK DI LINGKUNGAN KELUARGA TINJAUAN SOSIOLINGUISTIK - Baiq Yulia Kurnia Wahidah (Jurnal Ilmiah Global Education, 2023)
This study shows that there is an analysis of the use of language variations in the acquisition of the first language for toddlers who are in the family environment. Language acquisition has a very close relationship with language use. Language variations used in the family environment can affect a toddler's ability to develop the ability to communicate well with parents and those around them. This study took research subjects on children from the age of 3 years to 5 years. Thus, analysis of linguistic data will be a reference material in finding variations of the language obtained